Post-translational modifications talk and crosstalk to class IIa histone deacetylases - Guttzeit, Sebastian; Backs, Johannes (Journal of molecular and cellular cardiology, 2022)
Epigenetic modifications, such as histone or DNA modifications are key regulators of gene transcription and changes are often associated with maladaptive processes underlying cardiovascular disease. Epigenetic regulators therefore likely play a crucial role in cardiomyocyte homeostasis and facilitate the cellular adaption to various internal and external stimuli, responding to different intercellular and extracellular cues. Class IIa histone deacetylases are a class of epigenetic regulators that possess a myriad of post-transcriptional modification sites that modulate their activity in response to oxidative stress, altered catecholamine signalling or changes in the cellular metabolism. This review summaries the known reversible, post-translational modifications (PTMs) of class IIa histone deacetylases (HDACs) that ultimately drive transcriptional changes in homeostasis and disease. We also highlight the idea of a crosstalk of various PTMs on class IIa HDACs potentially leading to compensatory or synergistic effects on the class IIa HDAC-regulated cell behavior.